Optimization of Key Parameters for Coal Seam L-CO2 Phase Transition Blasting Based on Response Surface Methodology - Xuanping Gong; Xiaoyu Cheng; Cheng Cheng; Quangui Li; Jizhao Xu; Yu Wang (Applied Sciences)
Liquid carbon dioxide (L-CO2) phase transition blasting technology, known for its high efficiency, environmental friendliness, and controllable energy output, has been widely applied in mine safety fields such as coal roadway pressure relief and coal seam permeability enhancement. However, the synergistic control mechanism between L-CO2 blasting loads and in situ stress conditions on coal seam fracturing and permeability enhancement remains unclear. This study systematically investigates the key process parameters of L-CO2 phase transition blasting in deep coal seams using response surface methodology and numerical simulation. First, three commonly used L-CO2 blasting tubes with the overpressure of 150 MPa, 210 MPa, and 270 MPa were selected, and the corresponding material parameters and state equations were established. A dynamic mechanical constitutive model for a typical low-permeability, high-gas coal seam was then developed. A numerical model of L-CO2 phase transition blasting, considering fluid–solid coupling effects, was then constructed. Multiple experiments were designed based on response surface methodology to evaluate the effects of blasting pressure, in situ stress, and stress difference on L-CO2 fracturing performance. The results indicate that the overpressures of the three simulated blasting loads were 156 MPa, 215 MPa, and 279 MPa, respectively, and the load model closely matches the actual phase blasting load. L-CO2 blasting creates a plastic deformation zone and a pulverized zone around the borehole within 500 μs to 800 μs after detonation, with a tensile fracture zone appearing at 2000 μs. By analyzing radial and tangential stresses at different distances from the explosion center, the mechanical mechanisms of fracture formation in different blast zones were revealed. Under the in situ stress conditions of this study, the number of primary fractures generated by the explosion ranged from 0 to 12, the size of the pulverized zone varied from 1170 cm2 to 2875 cm2, and the total fracture length ranged from 44.4 cm to 1730.2 cm. In cases of unequal stress, the stresses display axial symmetry, and the differential stress drives the fractures to expand along the direction of the maximum principal stress. This caused the aspect ratio of the external ellipse of the explosion fracture zone to range between 1.00 and 1.72. The study establishes and validates a response model for the effects of blasting load, in situ stress, and stress difference on fracturing performance. A single-factor analysis reveals that the blasting load positively impacts fracture generation, while in situ stress and differential stress have negative effects. The three-factor interaction model shows that as the in situ stress and stress difference increase, their inhibitory effects become stronger, while the enhancement effect of the blasting load continues to grow. This research provides a theoretical basis for blasting design and fracture propagation prediction using L-CO2 phase transition blasting in the coal seam under varying in situ stress conditions, offering valuable data support for optimizing the process of L-CO2 phase transition fracturing technology.